A Cationic Barium Hydride Complex Supported by an NNNN‐Type Macrocycle. Issue 4 (14th November 2022) - Höllerhage, Thomas; Spaniol, Thomas P.; Englert, Ulli; Okuda, Jun
Abstract: The dibenzyl complex of barium [(Me4 TACD)Ba(CH2 Ph)2 ] was prepared by reacting [Ba(CH2 Ph)2 ] with NNNN‐type macrocycle Me4 TACD (Me4 TACD=1, 4, 7, 10‐tetramethyltetraazacyclododecane) and isolated as yellow crystals. Single crystal X‐ray diffraction revealed η 2 ‐ and η 3 ‐coordination of the benzyl groups. The benzylbarium cation in [(Me4 TACD)Ba(CH2 Ph)(thf)][B(C6 H3 ‐3, 5‐Me2 )4 ] was obtained upon protonolysis of the neutral bariumdibenzyl with the weak Brønsted acid [NEt3 H][B(C6 H3 ‐3, 5‐Me2 )4 ] and isolated as colorless crystals. When the benzylbarium cation was reacted with H2 (1 bar) in THF at room temperature, colorless crystals of the dinuclear hydride complex [(Me4 TACD)2 Ba2 (μ‐H)2 (thf)4 ][B(C6 H3 ‐3, 5‐Me2 )4 ]2 precipitated from the reaction mixture and characterized by single crystal X‐ray diffraction. The structural motif [Ba2 (μ‐H)2 ] 2+ was compared with that published in the literature. Hydrogenolysis of the dibenzyl [(Me4 TACD)Ca(CH2 Ph)2 ] under the same conditions resulted in decomposition. Abstract :